46 The Hidden Truth About Gender Bias in Surgery. A Systematic Review. (4th May 2021) - Wong, C; Lim, W H; Jain, S R; Ng, C H; Tai, C H; Devi, M K; Samarasekera, D D; Iyer, S G; Chong, C S
Abstract: Introduction: Gender discrimination remains pervasive in surgery, significantly impacting current and future surgeons and population health. This study analyses the gender barriers and critical retention factors for female surgeons and trainees in surgery. Method: Five electronic databases were searched till May 2020. Titles and abstracts were sieved, followed by a full text review. Data synthesis and inductive thematic analysis were conducted using the Thomas and Harden methodology. Result: 14 articles were included, involving 528 participants. Four themes were generated–unfavourable working environment, male-dominated culture, societal pressures and progress towards gender equality. Females in surgery often faced harassment, disrespect and perceptions of incompetence, resulting in hostile work conditions, which were aggravated by the inadequate support and mentorship. The persistence of male-dominated cultures was observed, with females facing prejudice and exclusion from professional and social circles. Differential treatment and higher expectations of female surgeons also arose from entrenched societal pressures. Despite these, increased acceptance of motherhood and greater recognition of contributions by female surgeons were reported, indicating some progress in gendered culture. Conclusions: There is a need to increase female surgical leadership and allocate resources to address the deep-rooted causes of biased surgical culture and ingrained perceptions, to achieve greater gender equality in surgery.